As relações públicas comunitárias como processo organizacional do Instituto Batucando a Esperança: proposta de um plano de ação de comunicação comunitária - PESTANA, Luany de Oliveira (2023)
The objective was to elaborate a community communication action plan for the Instituto Batucando a Esperança (IBE) - Vila Palmeira neighborhood in São Luís, MA with the purpose of assisting in its institutionalization process. The social institute aims to provide assistance to children and adolescents in situations of socioeconomic vulnerability, through the teaching of percussive music. For the theoretical development of this work it was necessary to use studies in the areas of: community communication, community public relations, organizational communication and communication in the third sector. The epistemological model was the interpretive one. The methodological implications were supported by a qualitative and quantitative (mixed) approach, bibliographic research, documentary research, case study and action research. These assumptions provided the choice of data collection techniques such as observation and questionnaire. The product, in turn, was built from the analysis of responses obtained in the questionnaires applied and meetings held with the stakeholders, parents/guardians and coordinators of the Institute. In this way, it was concluded that the practice of RPC within the community field consists of improving the relationship between the organization and its stakeholders, generating greater engagement and interaction, contributing, in the case in question, to the institutionalization of Batucando a Hope. Thus, it is understood that the community communication action plan is essential for the organizational structuring process of the institute, since it will guide the conduct and relationship of Batucando a Esperança with its stakeholders.